2006
DOI: 10.1111/j.1600-051x.2005.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fluorescence‐controlled Er:YAG laser radiation, the Vector™ system and hand instruments on periodontally diseased root surfaces in vivo

Abstract: Within the limits of the present study, it may be concluded that ERL and VUS enabled (i) a more effective removal of subgingival calculus and (ii) a predictable root surface preservation in comparison with SRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 43 publications
2
73
2
2
Order By: Relevance
“…The findings of our study related to dental plaque scores were in accordance with various other studies in which different methods were applied for the nonsurgical periodontal treatment. 13,22,23 During inf lammation, observable changes occur in the gingival tissues. To determine the extent of these gingival changes subjectively, dif ferent gingival indexes are used, such as the Löe and Silness Gingival index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of our study related to dental plaque scores were in accordance with various other studies in which different methods were applied for the nonsurgical periodontal treatment. 13,22,23 During inf lammation, observable changes occur in the gingival tissues. To determine the extent of these gingival changes subjectively, dif ferent gingival indexes are used, such as the Löe and Silness Gingival index.…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, in several studies, there was a significant decrease in the probing depth and bleeding upon probing and an increase of clinical attachment gain in patients with severe periodontitis treated with both VUS and hand instruments. [12][13][14] Numerous studies have demonstrated decreased levels of TNF-α following the non-surgical periodontal treatment performed with the hand instruments. 15,16 In the literature, there are no reports associated with the effects of vector ultrasonic system on the concentration of inflammatory mediators in patients with periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The laser-treated surfaces have high biocompatibility, and this is reflected in the clinical studies that have been undertaken to date and produced promising results [89][90][91][92][93][94][95]. …”
Section: Laser-induced Damage To Implant Surfacesmentioning
confidence: 99%
“…Preliminary clinical and histological results have shown that fluorescence-controlled (feedback system) Er:YAG laser radiation enabled an effective removal of subgingival calculus and a predictable root surface preservation in comparison with hand instruments (Schwarz et al 2006, Krause et al 2007). …”
Section: Periodontal Applications Of Diode Lasersmentioning
confidence: 99%